Grazing Diets of Mature Ewes in the Flint Hills Contain a Significant Proportion of Sericea Lespedeza - C. A. Sowers; J. D. Wolf; W. H. Fick; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:The objective of this study was to characterize diets selected by sheep grazing sericea lespedeza (Lespedeza cuneata) infested native tallgrass pastures and contrast these diets to those of cattle grazing the same range earlier in the grazing season. Multi-species grazing may provide an additional tool to aid landholders in the control of sericea lespedeza compared to cattle grazing only. Study Description:The study was conducted on 8 native tallgrass pastures grazed by more than 800 mature ewes. Pastures were infested with sericea lespedeza (basal frequency = 2.9 ± 2.43%) and stocked with yearling steers at a relatively high stocking rate (2.7 acres/steer) from April 15 to July 15 and subsequently grazed by sheep from July 30 to October 1. Fecal samples were collected from individual sheep on August 15 and on September 15 for 2 years. Samples were prepared and viewed under a compound microscope to identify and count plant fragments. These data were used to determine frequency at which each plant species appeared in diets selected by freely-grazing sheep. The Bottom Line:Sericea lespedeza comprised approximately 1.5% of sheep diets. Consumption at that level is likely sufficient to control seed production by that plant. Grazing of small ruminants in addition to cattle in a grazing system may provide landholders an additional tool for control of sericea lespedeza.
Keywords: botanical composition; grazing; sericea lespedeza; sheep